2022
DOI: 10.1002/ieam.4616
|View full text |Cite
|
Sign up to set email alerts
|

Are standard aquatic test species and methods adequate surrogates for use in environmental risk assessment of pesticides in tropical environments?

Abstract: In regulatory risk assessment, surrogate species of fish, aquatic invertebrates, and primary producers are tested to assess toxicity and subsequently the risk of pesticides to freshwater biota. This study evaluates whether the standard, surrogate test species (mostly temperate in latitudinal distribution) used in many parts of the world are suitable surrogates for first-tier risk assessments involving tropical freshwater biota. Data for the toxicity of pesticides to tropical fish, invertebrates, and primary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It has often been discussed that there is a deficiency in the availability of toxicity data derived for (Neo)tropical species (Niemeyer et al, 2017; Santos et al, 2023; Wang et al, 2019). Although research efforts have increased in the past decade (Figure 1), these have also been centered on a few local species from few (Neo)tropical countries (Figure 2).…”
Section: Difficulties In Comparing Tropical and Temperate Species Sen...mentioning
confidence: 99%
See 2 more Smart Citations
“…It has often been discussed that there is a deficiency in the availability of toxicity data derived for (Neo)tropical species (Niemeyer et al, 2017; Santos et al, 2023; Wang et al, 2019). Although research efforts have increased in the past decade (Figure 1), these have also been centered on a few local species from few (Neo)tropical countries (Figure 2).…”
Section: Difficulties In Comparing Tropical and Temperate Species Sen...mentioning
confidence: 99%
“…In addition, no consistent conclusion was drawn in these studies regarding the question to what extent and how toxicity data derived for temperate species can be used in tropical effect assessments. For example, several studies concluded that no additional assessment factor is warranted when using temperate toxicity data for effect assessments in other climatic zones (Daam et al, 2008; Hagen & Douglas, 2014; Khatikarn et al, 2018; Santos et al, 2023). Other studies, however, concluded that an additional assessment factor of 2 (Rijk, 2010; Wang et al, 2014), 2.2 to 6.2 (Hobbs, 2006), 4 (Wang & Leung, 2015), 5 (Wang et al, 2019), or even 10 (Kwok et al, 2007) should be applied when extrapolating temperate toxicity data to tropical regions.…”
Section: Previous Aquatic Species Sensitivity Comparison Studiesmentioning
confidence: 99%
See 1 more Smart Citation